Pengaruh Modul Sistem Informasi Akuntansi pada Enterprise Resource Planning terhadap Profitabilitas (Studi Kasus pada PT Prisma Harapan Tahun 2021) - R. Sasongko (Departement of Mathematics Education, 2023)
After three years running, the ERP implementation at PT Prisma Harapan did not produce results. Starting from these problems, it is significant to examine the effect of the accounting information system module (AIS or AIS) on Enterprise Resource Planning (ERP) on profitability. Starting from this background, the purpose of this study is to analyze the application of the Accounting Information System (AIS) module in Enterprise Resource Planning (ERP); analyze the effect of Accounting Information System (AIS) on Enterprise Resource Planning (ERP); analyze the effect of Accounting Information System (AIS) on company profitability; analyze the influence of Enterprise Resource Planning (ERP) on company profitability. Quantitative research approach, with survey method. The data processing technique uses SPSS. The results showed that ERP had a positive effect on profitability but not significant; ERP has a positive effect on SIA/AIS but not significant; SIA/AIS has a positive effect on profitability but not significant.